New horizons in the pharmacological management of venous thromboembolism - Andreas Verstraete; Quentin Van Thillo; Thomas Vanassche; Peter Verhamme (HemaSphere)
Abstract Many patients suffer from venous thromboembolism (VTE) and its consequences. Despite substantial advancements with the introduction of direct oral anticoagulants (DOACs), patients and clinicians still encounter challenges in the acute and long‐term management of VTE, such as recurrent events, anticoagulant‐related bleeding complications, and post‐thrombotic symptoms. Additionally, certain patient populations, including those with advanced kidney failure and liver cirrhosis and elderly individuals, were excluded from phase 3 clinical DOAC trials. Therefore, the call for innovative anticoagulants in the acute and long‐term management of VTE resonates, not only to mitigate long‐term recurrences and post‐thrombotic symptoms but also to maintain the delicate harmony of hemostasis. Novel targets within the coagulation and fibrinolytic system, as well as mechanisms governing adherence to the vessel wall, are currently being explored to address these unmet needs. First, factor XI inhibitors have shown promise in preclinical and phase 2 clinical studies to tackle thrombosis while preserving hemostasis, although phase 3 trials are required for confirmation. Next, there is interest to boost the endogenous fibrinolytic system, with α2‐antiplasmin, thrombin‐activatable fibrinolysis inhibitor, and plasminogen activator inhibitor‐1 emerging as potential attractive targets. Finally, strategies to inhibit the interaction between leucocytes and the vessel wall are also under exploration. This review provides an overview of the latest clinical advancements in the pharmacological management of VTE.